Collet-Sicard syndrome associated with occipital condyle fracture and epidural hematoma - Erol, Fatih Serhat; Topsakal, Cahide; Kaplan, Metin; Yildirim, Hanifi; Ozveren, Mehmet Faik (Yonsei Univ College Medicine, 2007)
A 31-year-old male was presented with a very rare case of ipsilateral palsies of the nerves IX through XII (Collet-Sicard syndrome) after a closed head injury. An occipital condyle fracture that was associated with epidural hematoma was diagnosed by computed tomography. The patient was conservatively managed, and following the treatment, partial neurological recovery ensued. The phenomenon of occipital condyle fracture involving the last four cranial nerve palsies is relatively rare. Although 3 cases of Collet-Sicard syndrome that were caused by an occipital condyle fracture has been reported, the association between condyle fracture and epidural hematoma has never been described before.
Keywords: Collet-Sicard syndrome; cranial nerve palsy; epidural hematoma; occipital condyl fracture